Pengawasan Hukum Platform E-Commerce Tiktok dan UMKM oleh KPPU Berdasarkan UU Nomor 5 Tahun 1999 - Andani, Debby Kusuma; Indarta, Didiek Wahju (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
E-commerce platforms in recent years have increased specifically, with the existence of e-commerce making an activity that has good prospects in the world of trade. Therefore, the existence of a platform used as e-commerce has an impact on MSME players, especially in the small business sectors in the market. KPPU as an institution has its duties and authorities in supervising this matter. The purpose of this study is to determine the Role and Effectiveness of KPPU in Supervising Tiktok and MSME E-commerce Platforms Based on Law Number 5 of 1999. This research uses the Normative Method by taking a statutory approach (statutes approach) to examine legal supervision of KPPU based on Law Number 5 of 1999, and also using the Concept Approach (Concep approuch) aims to provide linkage to the concept of business competition in Law Number 5 of 1999. KPPU plays an important role as a State institution given its duties and authorities. As the controller of power and position as laws and regulations related to unfair business competition and independent institutions, Related to the case of Tiktok merging its application into e-commerce, the new policy through the Minister of Trade Regulation Number 31 of 2023 which is an amendment to the Minister of Trade Regulation Number 50 of 2020 concerning Provisions for Business Licensing, Advertising, Coaching, and Supervision of Business Actors in Trade through the electronic system, It's official to close Tiktokshop and separate the application, it's just that those who get permission are social media but e-commerce. For this action, KPPU as the supervisor of business competition has not received a report related to allegations of Monopoly Practices and Unfair Business Competition.